2019
DOI: 10.1051/0004-6361/201833039
|View full text |Cite
|
Sign up to set email alerts
|

The EDIBLES survey

Abstract: We report cosmic ray ionization rates toward ten reddened stars studied within the framework of the EDIBLES (ESO Diffuse Interstellar Bands Large Exploration Survey) program, using the VLT-UVES. For each sightline, between two and ten individual rotational lines of OH + have been detected in its (0,0) and (1,0) A 3 Π − X 3 Σ − electronic band system. This allows constraining of OH + column densities toward different objects. Results are also presented for 28 additional sightlines for which only one or rather w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 62 publications
5
23
0
Order By: Relevance
“…Densities of up to ∼ 10 7 cm −3 have been reported (Keto & Caselli 2010;Caselli et al 2019), while the actual peak density in contracting cores is expected to reach much higher values before a protostar forms. The magnitude of the CR ionization rate ζ ion measured in the outer envelopes of molecular clouds (in a range of the gas column densie-mail: ivlev@mpe.mpg.de e-mail: ksilsbee@mpe.mpg.de ties around N ∼ 10 21 cm −2 ) varies significantly from one object to another (Indriolo & McCall 2012;Neufeld & Wolfire 2017;Bacalla et al 2019). Given uncertainties in the leading transport regime(s) governing the CR penetration into the clouds (Ivlev et al 2018;Silsbee & Ivlev 2019), this introduces significant uncertainty in the value of ζ ion near the center; available theories (Padovani et al 2018b) predict ζ ion ∼ 10 −17 − 10 −16 s −1 for N ∼ 10 23 cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Densities of up to ∼ 10 7 cm −3 have been reported (Keto & Caselli 2010;Caselli et al 2019), while the actual peak density in contracting cores is expected to reach much higher values before a protostar forms. The magnitude of the CR ionization rate ζ ion measured in the outer envelopes of molecular clouds (in a range of the gas column densie-mail: ivlev@mpe.mpg.de e-mail: ksilsbee@mpe.mpg.de ties around N ∼ 10 21 cm −2 ) varies significantly from one object to another (Indriolo & McCall 2012;Neufeld & Wolfire 2017;Bacalla et al 2019). Given uncertainties in the leading transport regime(s) governing the CR penetration into the clouds (Ivlev et al 2018;Silsbee & Ivlev 2019), this introduces significant uncertainty in the value of ζ ion near the center; available theories (Padovani et al 2018b) predict ζ ion ∼ 10 −17 − 10 −16 s −1 for N ∼ 10 23 cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…We need to understand the mechanisms controlling cosmic-ray penetration into the clouds better in order to explain our observations. Previous studies suggested that the cosmic-ray ionisation rate of molecular clouds in the Galaxy is at the magnitude of 10 −16 s −1 (Indriolo & McCall 2012;Indriolo et al 2015;Bacalla et al 2019). ζ CR can reach a higher value (∼10 −14 s −1 ) in regions close to supernovae remnants (e.g.…”
Section: Ionsmentioning
confidence: 98%
“…Estimates for the cosmic-ray ionization rate (ζ p ) in relatively low-density, predominantly atomic gas may be obtained from observations of OH + (e.g., Hollenbach et al 2012;Porras et al 2014;Bacalla et al 2019). The simple chemical model described by Porras et al, for example, which balances the most significant production and destruction processes, leads to ζ p ∼ 1.3 × 10 −10 n H N m (OH + )/N m (H).…”
Section: Cn Excitationmentioning
confidence: 99%
“…4.1.2), and assuming T = 80 K there (as in Porras et al), then that relationship between ζ p and the OH + abundance yields ζ p < 5.6 × 10 −17 s −1 . Inclusion of the effects of polycyclic aromatic hydrocarbons (PAHs) on the ionization (Hollenbach et al 2012;Bacalla et al 2019) then would imply ζ p < 1.9-2.8 × 10 −16 s −1 . These limits fall within the range of ionization rates (from several references) tabulated by Bacalla et al (2019) (all adjusted for the f value for the OH + λ3583.8 line from Hodges et al (2018)).…”
Section: Cn Excitationmentioning
confidence: 99%